Association of Ethnicity With Multisystem Inflammatory Syndrome in Children Related to SARS-CoV-2 Infection: An International Case-Referent Study - Middelburg, Judith G.; Crijnen, Thomas E. M.; D'Antiga, Lorenzo; Verdoni, Lucio; Chikermane, Ashish; Garg, Padma; Acharyya, Bhaswati C.; Pruccoli, Giulia; Schnapp, Aviad; Rauf, Abdul; Middelburg, Rutger A. (Frontiers in Pediatrics, 2021)
Background: It has been suggested that children and infants can develop multisystem inflammatory syndrome in children (MIS-C) in response to a SARS-CoV-2 infection and that Black children are overrepresented among cases. The aim of the current study was to quantify the association between Black, Asian, or other non-White genetic background and COVID-19-related MIS-C in children and infants. Methods: Eight different research groups contributed cases of MIS-C, potentially related to SARS-CoV-2 infection. Several sensitivity analyses were performed, including additional data available from the literature. Analyses were stratified by geographical region. Results: Seventy-three cases from nine distinct geographical regions were included in the primary analyses. In comparison to White children, the relative risk for developing MIS-C after SARS-CoV-2 infection was 15 (95% confidence interval (CI): 7.1 to 32) for Black children, 11 (CI: 2.2 to 57) for Asian, and 1.6 (CI: 0.58 to 4.2) for other ethnic background. Conclusion: Pediatricians should be aware of the fact that the risk of COVID-19-related MIS-C is severely increased in Black children.